Simulation of braking energy recovery for the metro vehicles based on the traction experiment system. (December 2017) - Ruigang, Song; Tianchen, Yuan; Jian, Yang; Hao, He
In this paper, a new onboard energy storage system (ESS) is designed. In addition, the experiment system is developed for the energy recovery of the metro vehicle braking. The proposed ESS is not connected to the DC bus, but to the brake chopper in the inverter. The ESS has a simple structure and high reliability due to its independence from the metro vehicle traction system, and it does not feedback the energy to the traction system. The mathematical model of traction dynamics was studied. A scaled experiment system is developed to simulate metro vehicle traction conditions and to test the characteristics of the ESS. The whole experiment system is modeled and simulated in the Matlab/Simulink software. The experiment results show that the highest recovery efficiency of the system is 84.6%. Both the simulation and the experiment results confirm the validity and the feasibility of the proposed ESS.